UJI TOKSISITAS EKSTRAK KARANG LUNAK SARCOPHYTON SP ASAL TIMOR TERHADAP LARVA ARTEMIA SALINA LEACH - Dhone, Beatrix S; Theo da Cunha, TheoTheo da Cunha; Darmakusuma, Dodi (Chemistry Notes, 2023)
Research on toxicity test of Sarcophyton sp. extract from Timor against Artemia s. Leach Nauplii has been conducted. Sarcophyton sp. from Paradiso beach, Kupang, was macerated in n-hexane, ethyl acetate, and methanol then each macerate was evaporated at 400C and 450C to dry. The dried extract resulted was tested its secondary metabolite content and toxicity using Brine Shrimp Lethality Test (BSLT). The results showed that the methanol extract contains saponins, phenols, and steroids while the ethyl acetate extract contains steroids and terpenoids. The toxicity test against artemia showed that the methanol extract from Sarcophyton sp. is very toxic to the nauplii with LC50 value of 29,56 ppm while the ethyl acetate extract is classified toxic and gave LC50 value of 34,11 ppm.